The Use of the "Early Weight Loss Nomograms" as Compared to a Standard Weight Loss Percentage Protocol Will Decrease Postnatal Formula Supplementation - ÖZEK, EREN; BİLGEN, HÜLYA SELVA (My University, 2021)
Introduction: We compared the number of babies who needed formula supplementation, based on the "Early Weight Loss Nomograms," with the hypothetical outcomes that would have occurred in the same cohort if they had been managed according to a "weight loss percentage" protocol. Subjects and Methods: This study included 308 newborns. Supplemental formula was provided to babies whose weight loss was more than the 95th percentile according to the "Early Weight Loss Nomograms." Pathological weight loss was defined as when a weight loss was >5% at the 24th hour or >8% at the 48th hour. The number of babies who would have needed formula supplementation according to those two strategies were compared. Results: The mean postnatal first-second day weight losses for vaginal and cesarean deliveries were 3.06% versus 4.7% and 4.5%, versus 5.8%, respectively, and were significantly higher for babies born by cesarean section (p = 0.001). We found that 89.4% of vaginal deliveries and 89.2% of babies born by cesarean section were exclusively breastfed when the nomograms were in use. If the daily weight loss strategy would be applied instead of the nomograms to the study cohort, the rate of exclusive breastfeeding would be significantly lower for babies born by cesarean section (64.2% versus 89.2%) (p = 0.001). Conclusions: The use of the Early Weight Loss Nomograms will decrease the rate of formula supplementation.
Keywords: “percentage of daily weight loss,”; formula supplementation; newborn, breastfeeding, “Early Weight Loss Nomograms,”